2024
DOI: 10.24084/repqj11.504
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution CFD modelling of Lillgrund Wind farm

Abstract: Abstract. We report on a fully dynamic simulation ofVattenfall's Lillgrund offshore Wind Farm, with a focus on the wake effects of turbines on the performance of individual turbines, and of the farm as a whole.The model uses a dynamic representation of a wind turbine to simulate interaction between the wind and the turbine rotors, calculating the instantaneous power output and forces on the air; this was embedded in a finite element, large eddy simulation (LES) computational fluid dynamics code. This model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…One may argue that it should not be expected that similar conclusions would be found when investigating different columns/rows (with or without a gap in between turbines in this case) of wind turbines, wind velocities and slightly different wake models. In that sense similar studies such as the ones performed by [11,13,14,23,[44][45][46] may complement each other. In addition, they highlight the strengths and limitations of each model/method and offer to researchers better possibilities to gain a deeper and more integrated insight into the particular usefulness of every model/method under different circumstances and cases.…”
Section: Resultsmentioning
confidence: 53%
“…One may argue that it should not be expected that similar conclusions would be found when investigating different columns/rows (with or without a gap in between turbines in this case) of wind turbines, wind velocities and slightly different wake models. In that sense similar studies such as the ones performed by [11,13,14,23,[44][45][46] may complement each other. In addition, they highlight the strengths and limitations of each model/method and offer to researchers better possibilities to gain a deeper and more integrated insight into the particular usefulness of every model/method under different circumstances and cases.…”
Section: Resultsmentioning
confidence: 53%
“…The turbine model developed here builds upon previous work, where dynamic torque-controlled actuator discs with active-pitch correction were used to model wind turbines [15] and wind farms [4,16]. In the present model, actuator line techniques [5] have been used to represent the rotor, whereby the blades themselves are not resolved, but the forces exerted by them on the fluid are still present.…”
Section: Turbine Formulationmentioning
confidence: 99%
“…One striking feature of these models is that, barring a few exceptions [13,14], the turbine support structure is not modelled explicitly, and so, only the rotors affect the downwind flow. It is quite likely that, in the mid-to-far wake region, wake effects due to the structure are not important in wind farms; indeed, previous, validated studies of single wind turbines [15] and wind farms [4,16] have indicated that the tower and nacelle have negligible impact on the wake and consequently the performance of downwind turbines. The pertinent question here is, then, can the same be said for tidal turbines sited in swiftly flowing water, whose density is over 800 times that of air?…”
Section: Introductionmentioning
confidence: 99%
“…The turbine model developed here builds upon previous work, where dynamic torque-controlled actuator discs with active-pitch correction were used to model wind turbines [14] and wind farms [4,15]. In the present model, actuator line techniques [5] have been used to represent the rotor, whereby the blades themselves are not resolved, but the forces exerted by them on the fluid are still present.…”
Section: Turbine Formulationmentioning
confidence: 99%
“…One striking feature of these models is that, bar a few exceptions [12,13], the turbine support structure is not modelled explicitly, and so only the rotors affect the downwind flow. It is quite likely that, in the mid-to-far wake region, wake effects due to the structure are not important in wind farms; indeed previous, validated studies of single wind turbines [14] and wind farms [4,15] have indicated that the tower and nacelle have negligible impact on the wake and consequently the performance of downwind turbines. The pertinent question here is, then, can the same be said for tidal turbines sited in swiftly flowing water, whose density is over 800 times that of air?…”
Section: Introductionmentioning
confidence: 99%